Penerapan Kuis Wordwall dalam Keaktifan Belajar Peserta Didik Kelas IV C SD Supriyadi Semarang - Rafidah, Huwaida Nur; Mudzanatun, Mudzanatun; Armin Wibowo, Sapto; Muzaki Assidiqi, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research regarding student innovation and activeness in learning can be an important basis for designing effective learning strategies. With the aim of research to find out the results of applying the WordWall quiz in active learning. This type of research uses a qualitative descriptive research method, with a case study research design. Data analysis techniques for data collection, data reduction, data presentation and drawing conclusions. with research subjects totaling 29 students from class IV C SD Supriyadi Semarang. Before implementing WordWall there were still many students who were not enthusiastic about learning. The use of WordWall media in learning has a positive influence on students' activeness in learning. WordWall can help teachers be more creative and make the learning environment interesting and fun because it focuses on students, is technology-based, and makes students feel comfortable and at ease while learning. Apart from that, WordWall media helps learning because it is fun and is useful for increasing student activity.